URGENSI PENGEMBANGAN BAKAT DAN KREATIVITAS ANAK SEKOLAH DASAR - Irwan Suhendra; Neviyarni, Zelhendri Zen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to reveal the urgency of developing creativity, interests, and talents in elementary school children through a literature review as the main method. The elementary school years are a strategic stage for fostering children's potential comprehensively. The method used is a literature review, analyzing various articles, books, and journals discussing creativity, talent, and elementary education. The findings indicate that creativity plays a crucial role in enhancing critical thinking, innovative thinking, and problem-solving skills, while talent is a natural potential that needs to be guided and developed from an early age. This research reveals that a supportive learning environment, child-centered learning approaches, and the active roles of teachers and parents significantly influence this developmental process. Therefore, an integrated educational strategy is needed to optimally foster the growth of creativity and talent among elementary school students. Keywords: development, creativity, talent, elementary school